La-containing SBA-15/H2O2 systems for the microwave assisted oxidation of a lignin model phenolic monomer - Gu, Xiaoli; He, Ming; Shi, Yijun; Li, Zhongzheng (Maderas. Ciencia y Tecnología, 2025)
A convenient and efficient application of heterogeneous Lanthanum-containing SBA-15 systems for the microwave assisted oxidation of a lignin model phenolic monomer, 3-methoxy- 4-hydroxybenzyl alcohol, is reported. Environmental friendly and low-cost H2O2 was used as the oxygen atom donor. The catalyst was prepared by immobilizing Lanthanum species on to the periodic mesoporous channels of siliceous SBA-15. Powder X-ray diffraction data and Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) revealed that the host retains its hexagonal mesoporous structure after immobilization and most of the lanthanum species are better dispersed in the calcined materials. The surface area and pore size of La/SBA-15 was considerably decreased indicating the intrapore confinement of the Lanthanum species. The activity of the La/SBA-15 was investigated in the oxidation of 3-methoxy-4-hydroxybenzyl alcohol in the presence of hydrogen peroxide as oxidant. 68% conversion of 3-methoxy-4-hydroxybenzyl alcohol to vanillin or other undetectable by-products was obtained after 30 min of reaction under 200W microwave irradiation, compared to a poor 25% degradation after 24 h under conventional heating. The possibility of recycling the catalyst was studied.